Analisis Pengaruh Tarif Pajak, Sanksi Pajak, Sosialisasi Pajak dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Jepara - Khuraida Rahmatika; Noor Salim (Jurnal Rekognisi Akuntansi, 2021)
The purpose of this study was to analyze the effect of tax rate, tax sanctions, tax socialization, dan tax services as well as the influence of obedience taxpayer to pay the vehicle tax in region jepara. Sampling of population quota is determined by random sampling dan the sample size of 100 respondents. The method used to analyze the data regression analysis of data previously tested prior to test reliability, validity, classical assumptions of normality dan statistics , to the classical assumption test consist of: multikoloniearity test, heterocendasity test, autocorrelation test. The results obtained indicate that the of tax rate, tax sanctions, tax socialization, dan tax services as well as the influence of obedience taxpayer to pay the vehicle tax in region Jepara.